"Through the looking glass: envisioning new library technologies" an experience you can feel: haptic technology. Issue 3 (2nd May 2017) - Fernandez, Peter
Abstract : Purpose: The previous column on educational trends briefly mentioned haptic technology in the context of the future of educational technologies (Fernandez, 2017). However, haptic technology is important enough to merit further consideration on its own terms. Haptic technology is a term that encompasses a set of rapidly evolving technologies centering on recreating the sense of touch, with a wide range of applications, and is poised to influence a wide range of industries and transform how we interact with technology. This paper aims to provide an overview of what haptic technology is and elucidate some of the crucial ways it is likely to develop in the future. Design/methodology/approach: At its most basic level, haptic technology provides sensory feedback. This can be in service of making an experience more interactive; for example, when playing a video game, the remote control might vibrate in response to what is happening on the screen. It can also provide a wider range of previously unexplored feedback – as when a cell phone vibrates to notify its owner that they have received a text message. Findings: As the technology around the sense of touch develops, it will have the capacity to provide richer experiences as well as new opportunities for communication. This column will provide an overview of what haptic technology is and elucidate some of the crucial ways it is likely to develop in the future Originality/value: A fundamental shift is underway in how we interact with our computers and devices. Sensation-based products are being launched across a variety of industries, including consumer electronics, automobiles and health care.